Incidental ameloblastoma diagnosed after treatment for childhood tumor - Alice Indini, MD; Roberto Luksch, MD; Carlo Patriarca, MD; Guido Petracco, MD; Paolo Ronchi, MD; Luigi Colombo, MD; Maura Massimino, MD (Elsevier, 2017)
Ameloblastoma is a rare odontogenic neoplasm accounting for 1% of all tumors of the jaws. It is rarely diagnosed in pediatric and adolescent age. Cancer treatment is a well-known risk factor for the onset of secondary malignancies among childhood cancer survivors, but any link between ameloblastoma and prior cancer treatments has yet to be explored. Here we report on two cases of ameloblastoma diagnosed in patients previously treated for tumors in pediatric age.